Automated Supra- and Infratentorial Brain Infarct Volume Estimation on Diffusion Weighted Imaging Using the RAPID Software - Lakatos, Lehel; Bolognese, Manuel; Müller, Martin; Österreich, Mareike; von Hessling, Alexander (Frontiers in Neurology, 2022)
Purpose: The present computerized techniques have limits to estimate the ischaemic lesion volume especially in vertebrobasilar ischaemia (VBI) automatically. We investigated the ability of the RAP-ID AI (RAPID) software on diffusion weighted imaging (DWI) to estimate infarct size in VBI in com-parison to supratentorial ischaemia (STI). Methods: Among 123 stroke patients (39 women, 84 men, mean age 66 ± 11 years) having under-gone DWI 41 had had a VBI and 82 a supratentorial ischaemia (STI). The infarct volume calculation by RAPID was compared to volume calculations by 2 neurologists using the ABC/2 method. For interreader and between-method analysis intraclass correlation coefficient (ICC), area under the curve (AUC) estimations, and bland-altman plots were used. Results: ICC between the two neurologists and each neurologist and RAPID were >0.946 (largest 95% CI boundaries 0.917- 0.988) in the STI group, and > 0.757 (95% CI boundaries between 0.544 and 0.982) in the VBI group. In the STI group AUC values ranged between 0.982 - 0.999 (95% CI 0.971-1) between the 2 neurologists and between 0.875 - 1 (95% CI 0.787 - 1) between the neurol-ogists and RAPID; in the VBI group they ranged between 0.925 and 0.965 (95% CI 0.801 - 1) be-tween the neurologists, and between 0.788 and 0.931 (95% CI 0.663 - 1) between RAPID and the neurologists. Compared to the visual DWI interpretion by the neurologists, RAPID did not recognize a substantial number of infarct volumes of ≤ 2 mL. Conclusion: The ability of the RAPID software to depict strokes in the vertebrobasilar artery system seems close to its ability in the supratentorial brain tissue. However, small lesion volumes ≤ 2 mL remain still undetected in both brain areas.